Planning Urban Waterfront Industrial Districts: Toronto's Ashbridge's Bay, 1889-1910 - Desfor, Gene (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 1988)
The process by which one particular section of Toronto's waterfront, Ashbridge's Bay, was developed during the 1889-1910 period is analysed in the context of broader industrialization and urban reform movements. Primary sources, largely from the Toronto Harbour Commissioners' Archives recently opened to the public, and the City of Toronto Archives, provide the basis for the analysis. Evidence demonstrates that Toronto's influential 1912 waterfront plan, crucial in reshaping the lakefront, was built on numerous previous schemes for improving the port, the harbour, and adjacent areas. Ownership of Toronto's waterfront remained under the control of civic authorities more from pragmatic considerations than from a commitment to serve community-wide interests.